USING LINGUISTIC DESCRIPTIONS WITH MULTI-CRITERIA DECISION AID APPROACHES IN URBAN ENERGY SYSTEMS - Afsordegan, Arayeh; Sánchez, Mónica; Agell, Núria; Gamboa, Gonzalo; Cremades, Lázaro V. (BDC. Bollettino Del Centro Calza Bini, 2014)
Multi-Criteria Decision Aid (MCDA) methods include various collections of mathematical techniques related to decision support systems in non-deterministic environments to support such applications as facility management, disaster management and urban planning. This paper applies MCDA approaches based on qualitative reasoning techniques with linguistic labels assessment. The aim of this method is ranking multi-attribute alternatives in group decision-making with qualitative labels. Finally this method is applied to a case of urban planning in selection of the less energy consumption project in a geographical area in Catalonia. Keywords: Multi-Criteria Decision Aid, qualitative labels, energy